Biomaterial Geotextile Berbahan Biomassa untuk Meningkatkan Produktivitas Pertanian di Desa Sidorejo Kabupaten Bojonegoro - Nikmatin, Siti; Husin, Abd Djamil; Mulyanto, Budi; Adiati, Rima Fitria (Jurnal Pengabdian UNDIKMA, 2025)
This community service program aims to develop sustainable geotextiles made from local biomass. It involves training farmers in their production as an effort to reduce plastic use, improve soil health, and increase yields of papaya and chili crops. This community service implementation uses a participatory approach targeting farmers who are members of the "Karya Tani" farmer group in Desa Sidorejo, Bojonegoro Regency, East Java, with a total of 25 participants. The results of this service indicate that plastic mulch can be replaced with geotextiles made from local biomass in maintaining soil moisture, weed control, sunlight absorption, and water management. The best results were obtained from coconut coir geotextiles compared to straw, yielding 500 kg of papaya harvest from a 0.25-hectare plantation. Ultimately, this community development project aims to promote sustainable agriculture, empower rural communities, and contribute to a circular economy.